E-Learning and Digital Education in the Twenty-First Century - Mahruf Shohel, M. C. (IntechOpen, 2022)
E-learning and digital education approaches are evolving and changing the landscape of teaching and learning at all levels of education throughout the world. Innovation of emerging learning technologies is assisting e-learning and digital education to meet the needs of the 21st century. Due to the digital transformation of everyday practice, the process of learning and education has become more self-paced and accessible at any time from anywhere. The new generations of digital natives are growing up with a set of skills through their engagement with the digital world. In this context, this book includes a collection of chapters to facilitate continuous improvements including flexibility and accessibility in e-learning and digital education by exploring the challenges and opportunities of innovative approaches through the lenses of current theories, policies, and practices.